PROBLEMATIKA IMPLEMENTASI MERDEKA BELAJAR P5 (PROJEK PENGUATAN PROFIL PELAJAR PANCASILA) DI SMA NEGERI 2 AIR SUGIHAN - Ayu Amelia; Segar Sukrun; Rita Sugiarti; Abdurrahmansyah (STKIP Subang, 2026)
This study aims to analyze the implementation problems of the P5 Program (Pancasila Student Profile Strengthening Project) within the Independent Learning policy at SMA Negeri 2 Air Sugihan. The study used a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the implementation of P5 has been carried out in accordance with the Independent Curriculum guidelines, but still faces various obstacles, such as teachers' limited understanding of the concept and technical implementation of P5, lack of supporting facilities and infrastructure, limited implementation time, and suboptimal training and mentoring. In addition, differences in student readiness and participation also pose challenges in project implementation. Nevertheless, the implementation of P5 has had a positive impact on strengthening students' character, creativity, collaboration skills, and social awareness. Therefore, it is necessary to improve teacher competency, support facilities, and cooperation between schools and related parties so that the implementation of P5 can run more effectively and achieve the goal of forming a Pancasila Student Profile optimally.